2018
DOI: 10.1152/jn.00355.2018
|View full text |Cite
|
Sign up to set email alerts
|

Movement and perception recalibrate differently across multiple days of locomotor learning

Abstract: Learning a new movement through error-based adaptation leads to recalibration of movement and altered perception of that movement. Although presumed to be closely related, the relationship between adaptation-based motor and perceptual changes is not well understood. Here we investigated the changes in motor behavior and leg speed perception over 5 days of split-belt treadmill adaptation. We specifically wanted to know if changes in the perceptual domain would demonstrate savings-like behavior (i.e., less recal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 27 publications
4
51
0
Order By: Relevance
“…Lastly, the limited washout of motor after-effects could also indicate that motor and perceptual after-effects are originated by partially distinct processes. This is supported by previous research showing that motor and perceptual effects exhibit different patterns of saving 25 and retention 11 , distinct adaptation rates 6,15 and uncorrelated amounts of adaptation 8,9,12,13 . They also exhibit different patterns of generalization to other limbs 17 or novel targets 18,19 .…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Lastly, the limited washout of motor after-effects could also indicate that motor and perceptual after-effects are originated by partially distinct processes. This is supported by previous research showing that motor and perceptual effects exhibit different patterns of saving 25 and retention 11 , distinct adaptation rates 6,15 and uncorrelated amounts of adaptation 8,9,12,13 . They also exhibit different patterns of generalization to other limbs 17 or novel targets 18,19 .…”
Section: Discussionsupporting
confidence: 86%
“…It has been shown that split-belt training can correct motor deficits 31,32 and it would be interesting to determine if it also corrects perceptual deficits as well. Of note, recent work indicates that perceptual changes in the estimation of speed are reduced with repeated exposure to the split condition 25 , suggesting that similar reduction would be observed in the shifts of limb position. Thus, there might be a limited long term effect of split-belt walking on perceptual changes.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Changes in afferent-based estimates of hand location seem to be a robust form of sensory plasticity, as evidenced by its relatively quick emergence (Ruttle et al, 2016), its persistence despite explicit adaptation (Modchalingam et al, 2019), and its preservation despite aging Vachon et al, 2019) and within other forms of perturbations (Cressman and Henriques, 2009;Ostry et al, 2010;Cameron et al, 2012;Leech et al, 2018;Sombric et al, 2019). Furthermore, the recalibration of proprioception is intact in people with mild cerebellar ataxia (Henriques et al, 2014), despite the cerebellum playing a crucial role in adaptation (Martin et al, 1996;Bastian, 2006;2008;Tseng et al, 2007;Synofzik et al, 2008;Taylor et al, 2010;Izawa et al, 2012;Wong et al, 2019).…”
Section: Persistent Shifts In Hand Localizationmentioning
confidence: 99%